A Systematic Review of Artificial Intelligence in Enhancing English Foreign Learners’ Writing Skill - Pratama, Aryawira; Sulistiyo, Urip (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This systematic review examines the impact of Artificial Intelligence (AI) on enhancing the writing skills of English foreign learners. It highlights how AI technologies, such as ChatGPT, provide immediate feedback on grammar, punctuation, and style, facilitating efficient revisions and fostering creativity through brainstorming and vocabulary suggestions. The review emphasizes personalized learning experiences by analyzing individual writing patterns, which allows for tailored resources that increase student engagement and motivation. Using the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) 2020 checklist, the study evaluates 22 peer-reviewed articles published in 2024, revealing that AI tools promote collaboration among students through peer feedback and shared projects, enhancing critical thinking and communication skills. Additionally, AI improves accessibility for learners with disabilities through features like text-to-speech and speech recognition. The findings suggest that as AI technology evolves, its integration into language education will significantly enhance teaching methodologies and learning outcomes. This research underscores the importance of adapting pedagogical practices to fully leverage AI’s potential in promoting effective language acquisition, particularly in writing, thereby providing valuable insights for future explorations of AI’s role in educational settings.